GE_GERICHTE A/3056/2014 vom 11. März 2015 - GE Cour de justice (2015)
DOMAINE PUBLIC ; PROPORTIONNALITÉ ; LIBERTÉ DE CONSCIENCE ET DE CROYANCE;LIBERTÉ D'EXPRESSION;LIBERTÉ D'INFORMATION;STAND D'INFORMATION | LDPu.12; LDPu.13; LDpu.15; RUDP.1